O processo de criação nas expedições experimentais multimídia - Nascimento, Otávio do (2017)
I decided to divide the thesis into 3 main chapters that covers, each one the 3 Expeditions; another one chapter describes their Creation Process and the last one I conclude with my Final Considerations. Chapter One is about the « Journey to the Center of the Earth » and it starts with the story of how we found the Tunnel and its state was when we first saw it. Then, I present a small part of the conversation Karman and I had in 2015, concerning the origins of the show’s creation process, illustrated with photos and sketches that I produced at that time. Next I start an approach (that I called Arraiolo) in which I explain my current ideas regarding documents produced by R. Karman as: "Assembly Schedule" where he describes the production phases and their dates, "Texts from the Expeditionary Manual "taken from the leaflet distributed to the participating public (named "expeditionary") where we placed a lot of information about the "trip” and "Texts of the Expedition", including the actors and scenic lines, as well as his comments. This material is complemented by initial sketches I drew from each idea generated in my creative process, photos and media material. This kind of continuous approach is also used in the other two subsequent chapters. "The Great Journey of Merlin" is Chapter Two’s central theme, beginning with the creation of the visual identity by me; then another piece of conversation I had with Karman where we covered the process of procedural research for the spaces and how it defined the scenes. Then the "Texts’ Creation Process" where Karman reports their genealogy: books, invited writers and texts by various authors; "History and General Data on the Expedition", "Mechanics of the Show: the Transportation", and "The Cost of the Show" where production processes, logistics, administration and factual information are analysed. From there I develop the script’s analysis, divided in four parts based on the locations: - "Travel Agency" showing descriptions, texts and comments of the seven initial scenes, which all happened in São Paulo, around Sumaré district, illustrated with sketches and photos. - "Landfill" with scenes 8 and 9 that happened at the Sanitary landfill in Perus (SP), (texts, sketches and photos). - "Polytheama" with scenes 10 and 11, (with 23 sub-scenes) that took place in Jundiai (SP) at the Polytheama Theater, - "Niniane Lagoon" analyses scenes 12 to the final 13, which happened in a lagoon around the now extinct Nivoloni Pottery. At the end of the chapter, there is a reproduction of articles commenting on the show, within the national and international media. by narrating the years of research and laboratories in areas equivalent to the original São Paulo Expedition, with the respective processes until the final stage of the Inflatable Installation at the Citizenship Hangar. Architectural plans, sketches, promotion materials, and in the end, articles published within the media illustrate Karman's explanatory narrative based on my comments in 23 scenes. I highlighted a special chapter at the end of this Expedition to analyse the Inflatable Installation and its difference from a simple theatrical scenario. This chapter also shows its "making of". (I also included a video as an appendix). Chapter Four deals with the "Expedition’s Creation Process Map" where the trajectory of processes is displayed on a graphic. The intention is to trace the process development from its formative origins to the final show in its variations through the seasons. In the same chapter, the item "Deepening the Process Topics", I explain in more detail specific aspects of the Creation Process. I've also inserted some "Testimonials from the Cast" only as a sample, since they are also displayed on video, in full at the Attachment. In the Final Considerations I approach the "Thesis Creation Process" where I describe what it meant to me to perform "An Academic Thesis made by an Artist". I explain the "Arraiolo" method of the Expeditions that I invented and I also added the "Theoretical Reflections on the Thesis’ Creation Process", in which I comment in topics, theoretical aspects of the conduction of the thesis researched by other authors. Finally, in the Attachments, essential parts are added to the corpus of the Thesis for documentary importance, offered in "digital media" (pen-drive). I gathered video documentaries of the Expeditions; Conversations between Karman and me in 2015; and other complementary digital documents